Pengaruh Pengalaman Traumatik Dengan Gangguan Stres Pascatrauma (Ptsd) Pada Remaja - Rinna Yuanita Kasenda; Rachelia Kimbal; ⁠Yerikho pratasik; Jonathan Tindas; Angelita Martono; Chrystilia Rengkuan (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study addresses the high risk of post-traumatic stress disorder (PTSD) in adolescents resulting from traumatic experiences during critical developmental stages. The research aims to examine the relationship and influence of traumatic experiences on PTSD levels in adolescents aged 13–19 years. A quantitative correlational method with purposive sampling was utilized. The population consisted of adolescents who experienced trauma in the past two years, sampling 50 participants. Instruments included a traumatic experience scale and a PTSD scale based on DSM-5 criteria, using a 1–5 Likert scale. Data analysis involved validity and reliability tests, Pearson Product Moment correlation, and simple regression. Results revealed a positive and significant correlation between traumatic experiences and PTSD levels (r=0.672; p<0.05), with traumatic experiences explaining 45% of PTSD variance. The study concludes the critical need for early detection and psychological intervention to mitigate trauma’s negative effects on adolescent mental health. Furthermore, strengthening social support and coping strategies is vital as protective factors.